The Use of Nuclear Imaging for Cardiac Resynchronization Therapy - Chen, Ji (Current Science Inc., 2010)
Cardiac resynchronization therapy (CRT) has shown benefits in patients with end-stage heart failure, depressed left ventricular (LV) ejection fraction (≤ 35%), and prolonged QRS duration (≥ 120 ms). However, based on the conventional criteria, 20% to 40% of patients fail to respond to CRT. Studies have focused on important parameters for predicting CRT response, such as LV dyssynchrony, scar burden, LV lead position, and site of latest activation. Phase analysis allows nuclear cardiology modalities, such as gated blood-pool imaging and gated myocardial perfusion single photon emission computed tomography (GMPS), to assess LV dyssynchrony. Most importantly, GMPS with phase analysis has the potential of assessing LV dyssynchrony, scar burden, and site of late activation from a single acquisition, so that this technique may provide a one-stop shop for predicting CRT response. This article provides a summary on the role of nuclear cardiology in selecting patients for CRT, with emphasis on GMPS with phase analysis.